Functionalized hydrogels in neural injury repairing - Zhao, Wenqian; Tu, Hui; Chen, Jianxiao; Wang, Jing; Liu, Haoting; Zhang, Fengshou; Li, Jing (Frontiers in Neuroscience, 2023)
Repairing injuries to the nervous system has always been a prominent topic in clinical research. Direct suturing and nerve displacement surgery are the primary treatment options, but they may not be suitable for long nerve injuries and may require sacrificing the functionality of other autologous nerves. With the emergence of tissue engineering, hydrogel materials have been identified as a promising technology with clinical translation potential for repairing nervous system injuries due to their excellent biocompatibility and ability to release or deliver functional ions. By controlling their composition and structure, hydrogels can be Functionalized and almost fully matched with nerve tissue and even simulate nerve conduction function and mechanical properties. Thus, they are suitable for repairing injuries to both the central and peripheral nervous systems. This article provides a review of recent research progress in functionalized hydrogels for nerve injury repair, highlighting the design differences among various materials and future research directions. We strongly believe that the development of functionalized hydrogels has great potential for improving the clinical treatment of nerve injuries.